A Novel NADP(+)- Dependent Dehydrogenase Activity for 7 α/β and 11 β-hydroxysteroids in human liver nuclei: A Third 11 β-Hydroxysteroid Dehydrogenase - Robinzon, B. (2009)
Human tissue from uninvolved liver of cancer patients was fractionated using differential centrifugation and characterized for 11βHSD enzyme activity against corticosterone, dehydrocorticosterone, 7α and 7β-hydroxy-dehydroepiandrosterone, and 7-oxodehydroepiandrosterone. An enzyme activity was observed in nuclear protein fractions that utilized either NADP(+) or NAD(+), but not NADPH and NADH, as pyridine nucleotide cofactor with K(m) values of 12 ± 2 and 390 ± 2 μM, compared to the K(m) for microsomal 11βHSD1 of 43 ± 8 and 264 ± 24 μM, respectively. The K(m) for corticosterone in the NADP(+)-dependent nuclear oxidation reaction was 102 ± 16 nM, compared to 4.3 ± 0.8 μM for 11βHSD1. The Kcat values for nuclear activity with NADP(+) was 1,687 nmol/min/mg/μmol, compared to 755 nmol/min/mg/μmol for microsomal 11βHSD1 activity. Inhibitors of 11βHSD1 decreased both nuclear and microsomal enzyme activities, suggesting that the nuclear activity may be due to an enzyme similar to 11βHSD Type 1 and 2.